Multiculturally competent intake interview with LGBTQI + clients. Issue 2 (3rd April 2019) - Oh, Seungbin; Kim, Nayoung; Bennett, Caitlyn McKinzie; Taylor, Dalena Dillman
Abstract: Multicultural counseling competencies (MCC) in an intake interview is the most fundamental component of affirmative counseling practice for individuals that identify as lesbian, gay, bisexual, transgender, queer (LGBTQ), or other sexual-relational orientation or gender identity. Despite the importance of counselors' MCC in the area of intake interviews, little practical guidance exists to help counselors conduct multicultural competent intake interviews. This article provides practical guidelines and strategies for counselors to engage clients in multiculturally competent intake interviews.